2003
DOI: 10.1088/0953-8984/15/17/308
|View full text |Cite
|
Sign up to set email alerts
|

Computer modelling of defect structure and rare earth doping in LiCaAlF6and LiSrAlF6

Abstract: This paper describes a computational study of the mixed metal fluorides LiCaAlF 6 and LiSrAlF 6 , which have potential technological applications when doped with a range of elements, especially those from the rare earth series. Potentials are derived to represent the structure and properties of the undoped materials, then defect properties are calculated, and finally solution energies for rare earth elements are calculated, enabling preferred dopant sites and charge compensation mechanisms to be predicted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 11 publications
1
30
0
Order By: Relevance
“…Sr-based colquiriite lattice is more disturbed as compared with Ca-based one. It is known that LiCaAlF 6 and LiSrAlF 6 crystals include both Schottky and Frenkel defects [5]. Interstitial F À ions are the main charge compensative defects in RE 3+ -doped LiCaAlF 6 and LiSrAlF 6 .…”
Section: Methodsmentioning
confidence: 99%
“…Sr-based colquiriite lattice is more disturbed as compared with Ca-based one. It is known that LiCaAlF 6 and LiSrAlF 6 crystals include both Schottky and Frenkel defects [5]. Interstitial F À ions are the main charge compensative defects in RE 3+ -doped LiCaAlF 6 and LiSrAlF 6 .…”
Section: Methodsmentioning
confidence: 99%
“…Higher thermal F-centers stability in LiCAF may be determined by the higher temperature of ionic diffusion-controlled process occurring at T >0.5 T melt as a rule (melting points are at 750 and 825 °C for LiSAF and LiCAF, accordingly). Experimental data [5] proved that Ce 3+ ions occupy Me 2+ sites (Me=Ca, Sr) and the activator center is ascribed to Ce [4]. Obtained results show that the F-coloration efficiency of both Ce-doped crystals is nearly three times higher than of pure ones.…”
Section: Discussionmentioning
confidence: 86%
“…the parameter a increases whereas c decreases with temperature increasing. In [4], a potential was fitted for the both structures to predict the form of defect disorder. It was shown that Li i + formation is the most likely form of the defect disorder in both matrices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations